Tatanan Indonesia Dalam Mewujudkan Pertumbuhan Ekonomi Berkelanjutan Melalui Green Economy - Khoirunisa Wahida; Hoirul Uyun (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Green Economy is an economic approach that focuses on sustainable development and utilization of resources, by integrating economic, environmental, and social aspects by involving changes in mindset and lifestyle. With the expectation that people are expected to adopt sustainable behaviors and consumption such as reducing waste, supporting environmentally friendly products, and recycling. The main goals of a green economy are to reduce negative impacts on the environment, including reduction of greenhouse gas emissions, protection of biodiversity, conservation of water resources, and effective waste management.  Green economy not only focuses on environmental protection, but also involves social and economic aspects. This includes improving social welfare and improving quality of life through sustainable job creation, increased access to basic services, and community empowerment in decision-making that impacts the environment. There are several important aspects in realizing a green economy through policies and regulations to encourage the transition to a sustainable economy that considers environmental and social aspects that support the green economy in realizing the transition to a sustainable economy. The second is investment in renewable energy that uses energy such as solar power, wind power, hydroelectricity, biomass and geothermal energy. The third is sustainable infrastructure development, the fourth is community empowerment and the fourth is collaboration between the public and private sectors.